Tviterasi, tviteraši or twitteraši? - Miličević, Maja (Slovenščina 2.0, 2016)
In this paper we discuss the parallel manual normalisation of samples extracted from Croatian and Serbian Twitter corpora. We describe the datasets, outline the unified guidelines provided to annotators, and present a series of analyses of standard-to-non-standard transformations found in the Twitter data. The results show that closed part-of-speech classes are transformed more frequently than the open classes, that the most frequently transformed lemmas are auxiliary and modal verbs, interjections, particles and pronouns, that character deletions are more frequent than insertions and replacements, and that more transformations occur at the word end than in other positions. Croatian and Serbian are found to share many, but not all transformation patterns; while some of the discrepancies can be ascribed to the structural differences between the two languages, others appear to be better explained by looking at extralinguistic factors. The produced datasets and their initial analyses can be used for studying the properties of non-standard language, as well as for developing language technologies for non-standard data.
Keywords: Croatian; hrvaščina; srbščina; Twitter (družabno omrežje); korpusi (jezikoslovje); računalniško posredovana komunikacija